Analisis Sistem Bank Wakaf Mikro Imam Syuhodo - Amri, Sholiqul (Universitas Batanghari Jambi, 2024)
Imam Syuhodo Micro Waqf Bank (BMW) is a sharia microfinance institution which aims to empower the community around the Imam Syuhodo Islamic Boarding School. The potential for growth and development of BWM Imam Syuhodo in Sukoharjo is expected to have great benefits for the Islamic-based economy. The policy regarding BWM as a sharia-based LKMS is intended so that BWM will become a pillar of strength in the sharia financial industry. The potential of the Imam Syuhodo Micro Waqf Bank certainly cannot be separated from the management system and Islamic good corporate governance (ICGC) implemented by the management at the BWM institution. The quality of the BWM institution depends on the implementation of a good business management system and an appropriate ICGC system. This research approach uses qualitative research. The aim of this research is to learn how to evaluate management, implement ICGC, and determine its effect on community empowerment. The results of the research reveal that the implementation of Islamic corporate governance at the Islamic microfinance institution Bank Waqf Mikro (LKMS BWM) Imam Syuhodo, when viewed using six indicators of Islamic corporate governance, has not been implemented in its entirety, where the indicators of trustworthiness, tabligh and fairness have been implemented well and to Siddiq, fathonah and sharia compliance indicators have not been implemented comprehensively and still need to be improved in their implementation